Penerapan Geographic Information System (GIS) Menggunakan Metode GeoJSON untuk Visualisasi Data Geospasial Sebaran UMKM Batik - M Al'Amin; Abdul Razak Naufal; Akrim Teguh Suseno (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Pekalongan City is one of the cities where batik grows. Until now, there are thousands of batiks MSMEs spread across many points in Pekalongan. To introduce batik MSMEs to the general public, a WebGIS-based platform is needed as an information center for Pekalongan batik. This research aims to build a website-based Geographic Information System (GIS) using GeoJSON as a platform for mapping the distribution of MSMEs of Batik and a digital batik literacy center in Pekalongan City. The GeoJSON method is used because it has the ability to read population data in only 14.7 seconds, loading geographic data via the GIS REST API usually takes 38.4 seconds, this makes it very suitable for use in web applications. Its simplicity, compatibility and platform independence have contributed to the geospatial community. GeoJSON is a natural fit with modern web technologies such as JavaScript, which makes it easy to use in web application development and integrates with web service APIs. The test scenario results obtained a total score of 85.8 and the System Usability Scale (SUS) test results obtained a total score of 83.5, which places it in the very good category. The SUS rating scale indicates that potential users find this application easy to use. The design of this application based on test results shows a better effect in terms of ease of use, apart from that, potential users generally give positive marks, so it can be concluded that the implementation of WebGIS using the GeoJSON method for visualizing the distribution of Batik MSMEs can be implemented very well.